2009
DOI: 10.1128/jvi.00316-09
|View full text |Cite
|
Sign up to set email alerts
|

The Six-Helix Bundle of Human Immunodeficiency Virus Env Controls Pore Formation and Enlargement and Is Initiated at Residues Proximal to the Hairpin Turn

Abstract: Residues that create the grooves of the human immunodeficiency virus type 1 (HIV-1) Env triple-stranded coiled coil (HR1) and the residues that pack into the grooves (HR2) to complete the formation of the six-helix bundle (6HB) were mutated. The extent and kinetics of fusion as well as pore enlargement were measured for each mutant. Mutations near the hairpin turns of each monomer of the 6HB were more important than those far from the turn, for both HR1 and HR2. This result is consistent with the idea that bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 56 publications
5
24
3
Order By: Relevance
“…K574 is highly conserved 24 and no substitution was observed at K574 in our study. Therefore, it may be concluded that drugs binding to K574 such as NB-2 and NB-64 will also be effective for our population.…”
Section: Qadir and Malikcontrasting
confidence: 67%
“…K574 is highly conserved 24 and no substitution was observed at K574 in our study. Therefore, it may be concluded that drugs binding to K574 such as NB-2 and NB-64 will also be effective for our population.…”
Section: Qadir and Malikcontrasting
confidence: 67%
“…A recent study of HIV-1 gp41 indicates that residues proximal to the hairpin turns of the 6HB are critical for membrane fusion, proposing that these residues are likely the first to be involved in the nucleation process between HR1 and HR2 and therefore crucial for driving the 6HB formation (54). Evidently, position 501 of JSRV and ENTV Env resides at the beginning of their putative hairpin turns, occupying the "d" position in the first 3-4 heptad repeat of HR2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The trimeric structure of gp41-HR1-54Q is stabilized by both inter-and intramolecular interactions between HR1 and HR2 (Shi et al, 2010). The exact order of molecular interactions between HR1 and HR2 that leads to 6HB formation is not known, although a leading working model suggests a zipping process along HR1-HR2 that begins at the C-and N-termini of respective domains in an anti-parallel fashion, with a central trimeric HR1 core (Markosyan et al, 2009). As such, we hypothesized that it might be possible to generate partially opened hairpin loop structures that might simulate fusion intermediates if HR1-HR1 or HR1-HR2 interactions were destabilized.…”
Section: Designing Gp41-hr1-54q Variants With Destabilized 6hbmentioning
confidence: 99%